C-arm cone-beam computed tomography-guided minimally invasive open excision of an osteoid osteoma undetectable on fluoroscopy: A case report. (2019) - Higuchi, Takashi; Yamamoto, Norio; Hayashi, Katsuhiro; Takeuchi, Akihiko; Abe, Kensaku; Taniguchi, Yuta; Araki, Yoshihiro; Tsuchiya, Hiroyuki
Highlights: A robotic C-arm cone-beam computed tomography (CBCT) system provides a clear intraoperative visualization of the osteoid osteoma. C-arm CBCT allowed precise access to the tumor, accurate tumor resection, and minimal sacrifice of the normal bone in osteoid osteoma surgery. Repurpose use of the dilator, retractor, and wider trephine tips achieved more conservative results with a smaller skin incision. Abstract: Introduction: The small size of a nidus and the extensive sclerosis around it often make it difficult to identify tumors from the surrounding normal bone by fluoroscopy, and a large amount of bone resection might be required to secure complete removal during osteoid osteoma surgery. In this report, we present the first case of radiographically invisible osteoid osteoma that was successfully resected under a robotic C-arm cone-beam computed tomography (CBCT) imaging system. Presentation of case: A 14-year-old boy presented with persistent pain around the left knee joint was diagnosed with osteoid osteoma of the left distal femur. Since the tumor was not detectable by intraoperative fluoroscopy, a CBCT system was used for guidance during an open tumor resection. For a less invasive surgery, we repurposed the dilator and retractor of the microendoscopic discectomy (MED) system and resected the tumor using the wider trephine tips for bone biopsy. At the final follow-up one year later, the function of the afflicted limb was normal with no complaint of any symptoms. Plain radiograph at the final follow-up showed new bone formation completely filling the bone defect, without local recurrence. Discussion: CBCT allowed for clear intraoperative visualization of the osteoid osteoma, thereby promising a secure resection and less invasive osteoid osteoma treatment. Furthermore, the repurposed use of the dilator and retractor of the MED system as well as the wider trephine tips for bone biopsy made the procedure less invasive. Conclusion: CBCT-guided minimally invasive open excision surgery could be a useful option for the management of radiographically invisible osteoid osteoma.